An analysis of citizen participation in service delivery in Zimbabwe's small towns: A case study of Chiredzi Town Council - Matsilele, Blessing (Rhodes University, Faculty of Humanities, Department of Sociology)
Over the years, there have been complaints of poor service delivery in Zimbabwe's Urban Councils. Newspapers in Zimbabwe have been filled with stories of poor service delivery and citizen grievances. Existing literature on service delivery has focused on the causes of poor service delivery, blaming them solely on the local government authorities. The literature has blamed poor service delivery in Zimbabwe on corruption, polarisation, politicisation, and incapacitation amongst other things. What is not highlighted is the role that citizens play and their responsibility in ensuring that there is proper service delivery. This thesis discusses the ways in which citizens participate in local government service delivery in Chiredzi which is an urban Council in Zimbabwe. To establish citizen participation in Chiredzi, this theory draws upon the social capital theory focusing on its trust, network, and norms aspect. Social capital facilitates an analysis of citizen participation and service delivery in Chiredzi. For this study,a qualitative research methodology was used. This methodology consisted of semi-structured telephone interviews with participants together with relevant documents. It was concluded that there is a need to educate citizens on their roles and responsibilities in local government to improve the state of service delivery.
Keywords: Municipal services -- Zimbabwe -- Chiredzi Rural District; Political participation -- Zimbabwe -- Chiredzi Rural District; Social capital (Sociology) -- Zimbabwe -- Chiredzi Rural District; Municipal services -- Zimbabwe -- Chiredzi Rural District -- Citizen participation; Community development -- Zimbabwe -- Chiredzi Rural District